Near-surface microrheology reveals dynamics and viscoelasticity of soft matter. Issue 48 (1st November 2018) - Liu, Wei; Gong, Xiangjun; Ngai, To; Wu, Chi
Abstract : We report the development of a microrheology technique that incorporates a magnetic-field-induced simulator on total internal reflection microscopy (TIRM) to probe the near-surface dynamics and viscoelastic behaviors of soft matter like polymer solution/gels and colloidal dispersions. Abstract : The development of experimental techniques able to probe the microscale viscoelastic properties of soft matter over a broad time scale is essential to uncover the physics that govern their behavior. Herein, we report the development of a microrheology technique that can determine the near-surface dynamics and viscoelastic behaviors of soft matter like polymer solution/gels and colloidal dispersions. Our approach combines a magnetic-field-induced stimulator with total internal reflection microscopy (TIRM) to apply mechanical loading (∼pN) to a micro-sized probe particle and capture its axial displacement near the surface with nano-scaled sensitivity. We demonstrate the use of this technique to measure the detachment of a colloid to a solid substrate and identify three quantitatively different regimes of mechanical coupling that differ in colloid–surface separation and interaction: exclusion, aging, and non-exclusion. We also apply it to study a physical gelation process of a volume-phase transition in thermosensitive microgels and a chemically cross-linked sol–gel transition of 4-arm star polymers by monitoring the evolution of complex modulus near solid surface with frequency, time, and separation distance. In contrast to passive microrheology techniques that rely on particle tracking, we can probe the viscoelastic behavior over five orders of magnitude in stiffness, from 10 −3 to 10 2 Pa, providing excellent coverage for dynamics and heterogeneous samples. We expect this technique will stimulate the development of new experimental methods to explore the complex microscale rheology of macromolecular networks, soft materials, and living cytoplasm.